2020
DOI: 10.3390/ijms21145084
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GLI3 Expression Mediates Chemotherapy Resistance in Acute Myeloid Leukemia

Abstract: Aberrant activation of the hedgehog (HH) pathway is observed in many neoplasms, including acute myeloid leukemia (AML). The glioma-associated oncogene homolog (GLI) transcription factors are the main downstream effectors of the HH signaling cascade and are responsible for the proliferation and maintenance of leukemic stem cells, which support chemotherapy resistance and leukemia relapse. Cytarabine (Ara-C)-resistant variants of AML cell lines were established through long-term cultivation with successively inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
(63 reference statements)
0
17
0
1
Order By: Relevance
“…One way to target GLI proteins could be by the activation of GLI3 R using hypomethylating agents [ 80 ]. Additionally, low levels of GLI3 result in a protective effect from the cytotoxic effects of Ara-C on LSCs or progenitors cells [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to target GLI proteins could be by the activation of GLI3 R using hypomethylating agents [ 80 ]. Additionally, low levels of GLI3 result in a protective effect from the cytotoxic effects of Ara-C on LSCs or progenitors cells [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that there was no expression of HH ligands in their cohort [ 81 ]. Recently, the group suggested that the downregulation of GLI3 may be associated with a low sensitivity to cytarabine (Ara-C) [ 82 ], which may indicate that low levels of this protein protect LSCs or progenitor cells from the effect of Ara-C. Furthermore, other studies that targeted the refractory/relapse population in AML have seen that overexpression of GLI1 leads to an increase in drug resistance [ 83 ].…”
Section: The Role Of Hedgehog In Amlmentioning
confidence: 99%
“…Protein isolation and western blots were performed as described before [ 48 ]. For analysis of phosphorylated proteins, cells were harvested and lysed with radioimmunoprecipitation assay (RIPA) buffer (89900, Thermo Fisher Scientific, Waltham, MA, USA) supplemented with protease and phosphatase inhibitors (cOmpleteTM Tablets, 11697498001, Roche, Basel, Swiss; Sodium orthovanadate, 13721-39-6, Fivephoton Biochemicals, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…ABCC4 inhibition can be accomplished with the use of inhibitors such as sorafenib or MK571 or by silencing it with siRNA ( Figure 3 b). Unfortunately, this strategy also sensitizes parental myeloids to Ara-C; therefore, it also induces toxicity and exacerbates hematological damage in healthy cells [ 51 , 79 , 80 , 81 , 82 , 83 ]. This is a serious drawback and remains a challenge to be addressed.…”
Section: Aml Cell Chemosensitization To Ara-cmentioning
confidence: 99%